Online Transportation Services for Educational Mobility in University Environments - Cendani, Zulva Tinesia Suci; Febrian, Putri Hana; Fauzi, Indra Nur; Mirdad, Mohammad Ayub; Haryanto, Albertus Eka Putra (Universitas Negeri Semarang, 2025)
Advances in digital technology have driven the emergence of online transportation services as an alternative mode of transportation for the public. The aim of this study is to provide a solution to public dissatisfaction with the quality of public transportation, particularly in terms of safety and reliability. Students, as part of the university community, also widely utilize these services. This study analyzes user perceptions, safety perceptions, and perceptions related to Gender, Disability, and Social Inclusion (GEDSI) regarding student satisfaction with online transportation services at Campus B, Airlangga University, Surabaya, Indonesia. This study used quantitative methods, analyzing primary data through binary logistic regression. The results indicate that payment systems, travel time, and the availability of disability-friendly services have a significant influence on user satisfaction. Ease of payment systems increases satisfaction because the transaction process is more practical. Short and timely travel times have also been shown to increase student satisfaction. This research contributes to the availability of disability-friendly services, as it has a positive impact by meeting the needs of people with disabilities more inclusively.